PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN MANGROVE UNTUK MENINGKATKAN EKONOMI DI DESA TAMBAKREJO KABUPATEN MALANG JAWA TIMUR - Lilik Sulistyowati; M. Fauzi Hafa; Andi Lopa Ginting; Darwiyati Darwiyati (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The purpose of this study were to analyze the comprehension and perceptions, degree of participation and the factors that can have an effect on the economic development of the community in managing mangrove forests. The data analysis method uses analytical descriptive. The results showed that: (1) Respondent has a proficient comprehension of mangroves as much as 52.6%, while for the perception of the majority of respondents have the perception of that 39.5% (2) The majority of respondents have a moderate level of participation (68.4%), (3) Factors affecting community participation are: sufficient tourism facilities, the number of available productive age workers is sufficient, thus making a positive economic impact for the benefit of the community. Suggestions for follow-up are as follows, the public of Tambakrejo needs an assistance in regards of innovation and marketing skills of products derived from mangrove, as well as an excellent waste management training in mangrove surrounding the coastal areas